Electrical properties of calcium phosphate/BZT bioglass-ceramics prepared by incorporation method - Siriporn Tigunta (2018)
Electrically active bioglass has received much attention as artificial bone graft material. In this study, the dielectric and piezoelectric properties of calcium phosphate-barium zirconium titanate bioglass-ceramics (CPGs-BZT bioglass-ceramics) were investigated as a function of BZT content. The BaZr 0 . 05 Ti 0 . 95 O 3 -40CaO- 45P 2 O 5 -15Na 2 O bioglass (CPG s/x BZT where x = 0, 10, 20, 30, 40, 50 wt.%) was prepared by an incorporation method. Crystallization temperature of each glass was measured by differential thermal analysis (DTA). XRD and SEM techniques were also used to characterize the phase formation and microstructure. The results showed that the BZT content caused an increase in dielectric and piezoelectric properties. The bioactivity of BZT/CPGs bioglass-ceramics was found to be higher than that of the pure CPGs after soaking in SBF for 14 days. © 2014 Taylor and Francis Group, LLC.